Global migration, entrepreneurship and society - Vershinina, Natalia; Rodgers, Peter; Xheneti, Mirela; Brzozowski, Jan; Lassalle, Paul (Emerald Publishing Limited, 2021)
In the field of business and management, the core concept associated with migration sees "difference and distance" as liabilities, whether they are national, cultural, geographic, or semantic. While existing research is valuable, recently it has been suggested that an emphasis on liabilities and adverse outcomes associated with such differences may hinder our understanding of the conditions that help to leverage the value of diversity in a wide range of contexts. Global Migration, Entrepreneurship and Society seeks to explore these seemingly interconnected processes, offering a safe space to critically examine the specific political contexts of excluded groups and develop a much-needed theoretical and policy-related set of writings that can cast light on the workings and complexities of processes of global migration, entrepreneurship and societal integration.
Includes index.
Keywords: Immigrant business enterprises.; Emigration and immigration -- Social aspects.; Entrepreneurship.; Business & Economics -- Entrepreneurship.; elektronické knihy; electronic books